(untitled) (Global Journal of Management and Business Research, 2018)
Customer relationship marketing is the core customer centric business strategy that aims at winning and keeping profitable customers. This study investigates the determinants of customer relationship marketing in banking industry with 502 respondents. For this paper a quantitative approach has been used. Primary and secondary data were used to conduct the study. To draw the valid conclusion and test them empirically, sophisticated statistical model as Exploratory Factor Analysis (EFA) has been used. To further determine the reliability of the data, Kaiser-Meyer_olkin (KMO) and Bartlett Test of sphericity were determined. The study reveals that four factors have been extracted from the analysis that together accounted 54.893% of the total variance. These factors were categorized as convenient opportunism, information sharing, completeness and desire.